Pengaruh Iman Dan Pendapatan Terhadap Penggunaan Uang Elektronik - Simatupang, Aisyah Defy Rahmayani (Zhafir | Journal of Islamic Economics, Finance, and Banking, 2020)
The application of electronic money in Indonesia has clear regulations, these regulations are regulated by the Central Bank. One of the regulations regarding electronic money (electronic money), among others, is Bank Indonesia Regulation Number 14 / 2PBI / 2012 concerning Amendments to PBI Number 11/11 / PBI / 2009 concerning the Implementation of APMK Activities. (Serfianto, 2012; 62) In an Islamic perspective, electronic money can be categorized as halal, if the fees charged to holders of electronic money (electronic money) are real costs and must be conveyed correctly to cardholders. Based on the approach used, the writer uses a quantitative research approach. Quantitative research is more oriented towards objective facts through concepts that are derived from the variables and translated into indicators by paying attention to aspects of validity and reliability. Quantitative research is divided into two types of research, namely, experimental research and non-experimental research. Non-experimental research is research where the researcher does not manipulate the independent variable, the researcher only examines what happens naturally or has happened, and examines how the variables are related. In preparing this proposal, the authors chose the type of non-experimental correlation research.